PEMANFAATAN GULMA AIR PERUPUK (Phragmites karka Trin) SEBAGAI TUMBUHAN PEREDUKSI LIMBAH CAIR INDUSTRI KARET - Deddy Dharmaji; Emmy Sri Mahreda; Danang Biyatmoko; Suhaili Asmawi (EnviroScienteae, 2015)
This research was aimed analyze the ability of perupuk (Phragmites karka Trin) in reducing of rubber industrial liquid waste polluters on the scale of the laboratory. The method used was the method of survey. The data laboratory test were tabulated and analyzed descriptively and the level of efficiency was calculated. Referring to South Kalimantan Governor Regulation Number 36/2008, the results showed that, TSS parameters started to be effectively reduced on day 10 with close to 84,33 mg/l (32.53%), BOD5 started to be effectively reduced on day 20 with close to 24.00 mg/l (99,29%), and COD started to be effectively reduced on day 20 with close to 44,65 mg/l (98,90%). Referring to the decision of the Minister of Environment No. KEP-78/MENLH/10/1995, the parameters of the Sulfide started to be effectively reduced on day 10 with close to 0.001 mg/l (93,75%) and Manganese start to be effectively reduced on day 20 with close to 0,70 mg/l (-134,00 %). Ph levels and temperature still normal condition.  Time retention was best accomplished on day 30 in reducing liquid waste rubber industry.